Relevance of mutations in protein deubiquitinases genes and TP53 in corticotroph pituitary tumors - Pękul, Monika; Szczepaniak, Magdalena; Kober, Paulina; Rusetska, Natalia; Mossakowska, Beata J.; Baluszek, Szymon; Kowalik, Artur; Maksymowicz, Maria; Zieliński, Grzegorz; Kunicki, Jacek; Witek, Przemysław; Bujko, Mateusz (Frontiers in Endocrinology, 2024)
Corticotroph pituitary neuroendocrine tumors (PitNETs) develop from ACTH-producing cells. They commonly cause Cushing's disease (CD), however, some remain clinically silent. Recurrent USP8, USP48, BRAF and TP53 mutations occur in corticotroph PitNETs. The aim of our study was to determine frequency and relevance of these mutations in a possibly large series of corticotroph PitNETs.Study included 147 patients (100 CD and 47 silent tumors) that were screened for hot-spot mutations in USP8, USP48 and BRAF with Sanger sequencing, while 128 of these patients were screened for TP53 mutations with next generation sequencing and immunohistochemistry. This is a provisional file, not the final typeset article USP8 mutations were found in 41% CD and 8,5% silent tumors, while USP48 mutations were found in 6% CD patients only. Both were more prevalent in women. They were related to higher rate of biochemical remission, non-invasive tumor growth, its smaller size and densely granulated histology, suggesting that these mutation may be favorable clinical features. Multivariate survival analyses did not confirm possible prognostic value of mutation in protein deubiquitinases. No BRAF mutations were found. Four TP53 mutations were identified (2 in CD, 2 in silent tumors) in tumors with size >10mm including 3 invasive ones. They were found in Crooke's cell and sparsely granulated tumors. Tumors with missense TP53 mutations had higher TP53 immunoreactivity score than wild-type tumors. Tumor with frameshift TP53 variant had low protein expression. TP53 mutation was a poor prognostic factor in CD according to uni-and multivariate survival analyses in spite of low mutations frequency.We confirmed high prevalence of USP8 mutations and low incidence of USP48 and TP53 mutations. Changes in protein deubiquitinases genes appear to be favorable prognostic factors in CD. TP53 mutations are rare, occur in both functioning and silent tumors and are related to poor clinical outcome in CD.